2018
DOI: 10.1186/s12889-018-5999-z
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting lifestyle of university students in Saudi Arabia: a cross-sectional assessment

Abstract: BackgroundCollege is a critical time where students are more prone to engage in risky health behaviors known to negatively affect well-being, such as physical inactivity, stress, and poor dietary habits. A health promoting lifestyle is an important determinant of health status and is recognized as a major factor for the maintenance and improvement of health. This study was designed to assess the health-promoting lifestyle of students in health colleges and non-health colleges in Saudi Arabia.MethodsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
150
7
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 47 publications
21
150
7
12
Order By: Relevance
“…In 2018, Almutairi et al conducted a study titled "Health Promoting Lifestyle of University Students in Saudi Arabia." e study reported that approximately 20% of participants were overweight, while 11.3% were obese [26]. Reports have revealed that a majority of both college and school students do not attend educational programs on health care [20,27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2018, Almutairi et al conducted a study titled "Health Promoting Lifestyle of University Students in Saudi Arabia." e study reported that approximately 20% of participants were overweight, while 11.3% were obese [26]. Reports have revealed that a majority of both college and school students do not attend educational programs on health care [20,27].…”
Section: Discussionmentioning
confidence: 97%
“…It is with this goal that we translated, designed, and tested the psychometric properties of the Arabic MIN-SC, which was determined to be a valid and reliable tool for assessing nutrition self-care among Saudi students. e need for this investigation was supported by numerous studies showing that school students do not sufficiently adhere to recommended physical activity and healthy eating habits [25,26]. In one study conducted using a convenience sample of school children to measure self-care, only 2.5% of the children had healthy practices, while 6.9% showed unhealthy behaviors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of Almutairi et al [38] empirically evaluated the factors that promote a healthy lifestyle among college students. The author used a descriptive cross-sectional study design to gather data from 1656 students from November 2016 to January 2017 at King Saud University in Saudi Arabia.…”
Section: Health Concerns In Saudi Arabiamentioning
confidence: 99%
“…de vida tem sofrido significativas mudanças, pois, nessa fase, há mudanças nas rotinas desses jovens e hábitos de saúde que passam a explicar ocorrência de agravos à saúde, nos quais o comportamento do indivíduo tem papel importante 2,3 . O ingresso no ensino superior é caracterizado por profundas mudanças de ordem social e comportamental, as quais podem levar a alterações em seus estilos de vida 4,5 .…”
unclassified
“…A aquisição de hábitos saudáveis como prática de atividade física, alimentação balanceada, comportamento preventivo e melhoria do sono podem reduzir os fatores de riscos para o desenvolvimento de doenças cardiovasculares, sendo, portanto, ações de baixo custo, quando comparadas com os ascendentes orçamentos dos tratamentos medicamentosos e dependentes de alta tecnologia 2,3,4 .…”
unclassified